Users' perceptions on parking utilization pattern at park-and-ride facility in Putrajaya Sentral - Syed Adnan, Sharifah Adibah Alyia; Kadar Hamsa, Abdul Azeez (Kulliyyah of Architecture and Environmental Design, IIUM, 2011)
The increasing number of private vehicles in Federal Territory of Kuala Lumpur and Putrajaya has created inadequate parking spaces and traffic congestion. The limited parking spaces for the public at Government complexes and its surroundings in Putrajaya had lead to the increasing number of illegal parking. As an initiative to encounter this problem, the concerned authority had provided the park-and-ride facilities at public transportation tenninal in Putrajaya. The provision of park-and-ride scheme would obviously promote the use of rail transit, thus shifting the users from using motorcar to public transport. Putrajaya Sentral is the main public transportation hub of Putrajaya which provides multi-modal public transportation services such as Express Rail Link (ERL), intercity buses, intra-city buses namely as 'Nadi Putra', express buses and taxi services. However, the existing parking spaces at the park and ride facility in Putrajaya Sentral are not fully utilized. Thus, this paper highlights the user's perceptions on parking utilization pattern at Putrajaya Sentral park and ride facility in order to examine the current parking demand at the parking facility. Parking inventory survey to determine existing physical conditions of the parking facility and questionnaire survey to evaluate the perceptions of the users on the parking usage pattern were administered. The findings showed that most of the users (78%) parked their vehicles for longer duration (more than eight hours). The multi-storey parking facility was found to have higher demand than surface parking due to minimal parking fees and longer operation hours. The major factors that influenced the users in using the park-and-ride facility are "avoiding traffic congestion", "convenience of travel with public transport", "less stress by travelling with public transport" and "parking at destination are too expensive". Few recommendations to overcome the identified problems and conclusions are also drawn.